Increasing prevalence of thyroid autoimmunity in childhood type 1 diabetes in the pre-COVID but not during the COVID era - Herczeg, Vivien; Muzslay, Eszter; Czipó, Diána; Terkovics, Lili; Takács, Johanna; Garai, Réka; Kovács, Fanni; Luczay, Andrea; Körner, Anna; Tóth-Heyn, Péter (Frontiers in Endocrinology, 2025)
IntroductionStudies assessing longitudinal changes in the prevalence of autoimmune thyroiditis (AIT) among the pediatric population are limited. During the COVID-19 era, several papers proposed a rise in AIT cases. Our study aimed to analyze the prevalence of thyroid autoimmunity (TA) over a 10-year period spanning pre-pandemic and pandemic years in a population who are regularly screened for thyroid disturbances.Materials and methodsThis single-center retrospective cohort study analyzed data from 1,361 children and young adults with type 1 diabetes (T1D) treated between 2013 and 2022 in Hungary’s largest pediatric endocrinology center. Results of anti-thyroid autoantibodies (anti-thyroid peroxidase/ATPO/and antithyroglobulin/ATG/), thyroid function tests (TFTs) and thyroid ultrasound examinations were obtained. Annual prevalence rates of TA and ultrasound-proven thyroiditis were calculated. Mean (± SD) follow-up period was 4.7 (± 2.8) years.ResultsThe overall prevalence of TA among our T1D children was 22.8% ([20.3;25.5], 310 cases) with significantly more girls affected (p<0.001). From 2013 to 2022, TA prevalence rose from 15.9% to 20.6% (p=0.041). The increase was detected during the pre-pandemic years but not in the COVID-19 era. Ultrasound-confirmed thyroiditis was present in 80.0% of examined TA cases. Ultrasound positivity rate was stable during the study period. Among our children with TA, 28.5% exhibited clinically relevant thyroid-stimulating hormone (TSH) abnormalities (most commonly subclinical hypothyroidism) and/or were prescribed thyroid medication. Children with AIT had a significantly elevated risk of thyroid dysfunction compared to those with only thyroid autoantibody positivity (p<0.001).ConclusionOur results show a rise in the prevalence of thyroid autoimmunity among T1D children over the past decade, but our data do not support the assumed role of SARS-CoV-2 in the development of the disease.